Integrated Primary And Supportive Care Models For Older Adults: The Combined Role Of Family Medicine, Pharmacy, Nursing, And Social Work In Improving Healthcare Quality (The Review of Diabetic Studies, 2025)
Background: Rapid population aging has increased the demand for coordinated, patient-centered healthcare models addressing the complex medical, functional, and social needs of older adults.Objective: To examine integrated primary and supportive care models and evaluate the combined role of family medicine, pharmacy, nursing, and social work in improving healthcare quality for older adults.Methods: A comprehensive literature review of multidisciplinary geriatric care models published in peer-reviewed journals was conducted, focusing on quality of care, patient safety, clinical outcomes, and system performance.Results: Evidence indicates that integrated care models improve medication safety, chronic disease control, functional status, care coordination, and patient satisfaction while reducing hospitalizations and fragmented care.Conclusion: Integrated primary and supportive care models are essential for achieving high-quality, sustainable elderly healthcare. Strengthening interdisciplinary collaboration is critical for future health system transformation.